Combination of intravitreal corticosteroid with anti-VEGF in macular edema secondary to retinal vein occlusion - Valášková, Jela; Popov, Ivajlo; Krásnik, Vladimír (Czech and Slovak Ophthalmology, 2017)
Purpose: functioal and anatomical results afer combinationof intravitreal dexamethasone implant with anti-VGF bevacizumab in macular edema secondary to retinal ein occlusion. Methods: Retrospectie analysis of 50 patints, average age 72 years, 15 men and 35 women. Inclusion criteria for treatment were retinalvein occlusion, best corrected visual acuity (BCVA) more than 20/200 and macular edema more than 250 μm. Algorithm of treatment was dexamethason, anti-VGF (bevacizumab), dexamethason. Applicationof anti-VGF bevacizumab was in interval between two applicationsof dexamethasone, for the fist timein every patiet. If there were nonperfusion areas on fluoesceine angiography (FA), or ischemia on slit lamp, repeatedly. Patiets observed for 12 months at least. This cohort included patiets with branch retinalvein occlusion together with central retinalvein oc-clusion. This is an evaluationof nonperfusion areas based on FA, BCVA, macular edema on optial coherence tomography (OCT) and number of reapplicationof anti-VGF bevacizumab. Observed adverse efects are elevationof intraocular pressure and number of patiets who underwent cataract surgery. Results: The gain of 8 letters in 1st month after 1st application of dexamethasone, central retinal thickness (CRT) reduced from 512 μm to 318 μm in average. 33 patients get 1, 3 patients get 2 and 14 patients 3 injections of bevacizumab. On the day of 2nd application of dexamethasone, in 7th month in average, the CRT increased on 465 μm, and 1th month after, the gain from the baseline was 10 letters and CRT reduced on 380 μm. All the pa-tients were phackic at the baseline, 18 (36 %) patients underwent cataract surgery with intraocular lens implantation. Transient elevation of intraocular pressure in 15 (30 %) eyes, treated by local therapy. Conclusion: Combination of intravitreal dexamethasone implant with anti-VEGF bevaci-zumab is functionally and anatomically effective.
Keywords: Statistics as Topic; Female; makulární edém; injekce intravitreální; statistika jako téma; výsledek terapie; ženské pohlaví; Macular Edema; Retina; lidé; bevacizumab; Treatment Outcome; Aged, 80 and over; hormony kůry nadledvin; Adrenal Cortex Hormones; Intravitreal Injections; retrospektivní studie; Male; Bevacizumab; Aged; dexamethason; Dexamethasone; Retinal Vein Occlusion; kombinovaná farmakoterapie; okluze retinální žíly; lidé středního věku; retina; senioři nad 80 let; senioři; mužské pohlaví; zraková ostrost; Visual Acuity; Retrospective Studies; Middle Aged; Drug Therapy, Combination; Humans